PERSONALITY AND SOCIAL SUPPORT AS PREDICTORS OF LIFE SATISFACTION OF NIGERIAN PRISONS OFFICERS - Ike E. Onyishi; Obinna E. Okongwu; Fabian O. Ugwu (European Scientific Journal, ESJ, 2012)
The study examined the relationship among personality, social support and life satisfaction among 601 employees of the Nigerian Prisons Service in a southeastern state in Nigeria. Data were collected using Life Satisfaction Index-Short Form, The Big Five Inventory, and Multidimensional Scale of Perceived Social Support. The result of the multiple regression analyses showed that personality is a significant predictor of life satisfaction. Specifically, extraversion, agreeableness, conscientiousness, and neuroticism were found to predict life satisfaction. The results also showed that social support is positively related to life satisfaction. Friends support, significant others support, and family support were significant predictors of life satisfaction among the participants. The implications of these results to research and clinical practice were discussed.